Comparison of the effects of substrate temperature and 2% molecular hydrogen annealing on the optical GAP OF a-Ge thin films . - K., G. Saw
Efforts are being directed towards using microcrystalline tetrahedral semiconductor material for better efficiency in thin film solar cells. 1 Since microcrystallinity is associated with increasing deposition temperature and annealing temperature, the effect of both these temperatures on the optical bandgap would be interesting to be compared.